Literasi Digital Pemimpin Sekolah dan Aktualisasi Dakwah Bil-Qalam di Media Sosial pada Generasi Muda - Moh AmirChoiri; Mulyadi Mulyadi; Ahmad Syukron; Fauziah Astuti (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This study aims to investigate how school leaders' digital literacy influences Muslim youth in transforming passive smartphone consumption into active religious expression through digital written propagation (dakwah bil-qalam). Employing a qualitative hermeneutic phenomenological framework, this research explores the lived experiences of three school leaders and eight Muslim teenagers across three Islamic senior high schools in West Java. Data collection was executed using semi-structured interviews, digital textual observations of social media feeds, and institutional documentation analysis, processed through the modified Colaizzi method. The findings demonstrate that a school leader’s comprehensive digital leadership creates an institutional scaffolding of psychological safety, which directly minimizes adolescent peer anxiety and digital surveillance barriers. The research novelty lies in its structural integration of Islamic educational management, communication, and pedagogy, demonstrating that visionary governance can successfully redirect passive screen-time behaviors into sustainable, text-based spiritual contributions within the contemporary digital ecosystem.